2008
DOI: 10.1109/jlt.2008.2004923
|View full text |Cite
|
Sign up to set email alerts
|

Coupled Lasers Rotation Sensor (CLARS)

Abstract: Abstract-We study the lasing eigen-modes and dynamics of circular array of coupled lasers in a rotating framework for ultrasensitive integrated optical rotation sensing applications. The dependence of the mode and frequency splitting on the array parameters and pumping level is studied in details. The impact of structure variations and disorder such as variations of the resonance wavelength of the individual cavities and the inter-cavity coupling is studied and found to generate a "dead-zone" which limits the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…Moreover, to achieve an ultrasensitive gyro, some other approaches, including the use of rotation-induced superstructure and circular array of coupled lasers, were proposed and studied. 17,18 Here we share the same understanding in Ref. 16 that the sensitivity is enhanced, not so much by slow light in structure as by the structure dispersion property which makes slow light a resultant phenomenon.…”
supporting
confidence: 73%
“…Moreover, to achieve an ultrasensitive gyro, some other approaches, including the use of rotation-induced superstructure and circular array of coupled lasers, were proposed and studied. 17,18 Here we share the same understanding in Ref. 16 that the sensitivity is enhanced, not so much by slow light in structure as by the structure dispersion property which makes slow light a resultant phenomenon.…”
supporting
confidence: 73%
“…Recent studies have shown that the employment of slow-light structures (SLS) in the rotation sensor can enhance the achievable sensitivity by orders of magnitudes [3][4][5][8][9] (for a given footprint). In particular, when the SLS comprises microcavities, it can be shown that the rotation directly modifies the dispersion relation of the SLS, thus generating substantially larger phase shifts compared to the classic Sagnac effect 5 .…”
Section: Why Slow Light?mentioning
confidence: 99%
“…Most of the available rotation sensors are wired and/or composed of active elements such as microwave gyroscopes [1], fiber-optic sensors [2], chirped fiber grating rotation sensor [3], coupled lasers rotation sensor (CLARS) [4], optical fiber rotation sensors [5], and surface acoustic wave (SAW) rotation sensors [6], [7]. In [8], a MEMS high-speed angular sensor has been reported, which can be considered as a semi-active design and is capable of wirelessly measuring the angular movement.…”
mentioning
confidence: 99%